Learned Helplessness and Its Relationship to Goal Orientations and Implicit Theory of Intelligence - Taieh, Refaeh; AL-Zghoul, Rafe (Jordan Journal of Educational Sciences, 2015)
This study aimed to investigate learned helplessness and its relationship to goal orientations and implicit theory of intelligence. To achieve the study goals, learned helplessness, goal orientation and implicit theory of intelligence scales were used on a sample consisting of 348 male and female students from Yarmouk University. The results showed that learned helplessness level was low, goal orientation: master, and performance-avoidence levels were high, while performance-approach, and fixed intelligence levels were moderate , and incremental intelligence level was high. It also showed no significant differences due to sex in learned helplessness, while there were significant differences due to college in the favor of humanity colleges, and significant differences due to sex in mastery and performance-avoidance goal orientation in favor of females. And it revealed significant differences in performance approach goals and fixed intelligence due to college in favor of humanity colleges. There were no significant differences due to sex in fixed and incremental intelligence. A negative relationship was found between learned helplessness, mastery and performance approach goal orientation and incremental theory of intelligence, while there is a positive relationship between learned helplessness, performance avoidance goals, and fixed intelligence